Intrinsic links among sex, emotion, and reproduction - Yang,L; Comninos,AN; Dhillo,WS (Cellular and Molecular Life Sciences, 2018)
Species survival is dependent on successful reproduction. This begins with a desire to mate, followed by selection of a partner, copulation and in monogamous mammals including humans, requires emotions and behaviours necessary to maintain partner bonds for the benefit of rearing young. Hormones are integral to all of these stages and not only mediate physiological and endocrine processes involved in reproduction, but also act as neuromodulators within limbic brain centres to facilitate the expression of innate emotions and behaviours required for reproduction. A significant body of work is unravelling the roles of several key hormones in the modulation of mood states and sexual behaviours; however, a full understanding of the integration of these intrinsic links among sexual and emotional brain circuits still eludes us. This review summarises the evidence to date and postulates future directions to identify potential psycho-neuroendocrine frameworks linking sexual and emotional brain processes with reproduction.